Prebiotics: Trends in food, health and technological applications - Farias, David de Paulo; de Araújo, Fábio Fernandes; Neri-Numa, Iramaia Angélica; Pastore, Glaucia Maria (Trends in food science & technology, 2019)
Currently, there is a growing interest in the identification of new molecules that promote health and exhibit potential for technological applications. Prebiotics are functional ingredients naturally occurring in some plant and animal foods that have received considerable attention from the pharmaceutical and food industries due to their positive health effects. With an increasing demand, it is necessary to develop strategies that aim to increase the production of prebiotics in order to meet the needs of the consumer market. This review aims to emphasize the potential of innovation and the importance of prebiotics (non-digestible carbohydrates) as health promoters and their use as an ingredient for food elaboration, and to discuss the use of microorganisms and enzymes as strategies to prepare them. The intake of prebiotics plays an important role in modulating the intestinal microbiota, increasing the production of short chain fatty acids (SCFA) and reducing the risk of development of various diseases such as colon cancer, irritable bowel syndrome, type 2 diabetes mellitus, and obesity, among other disorders. The use of these compounds can improve the nutritional, physical-chemical, and sensory characteristics of food. The synthesis of non-digestible carbohydrates by microorganisms and enzymes are strategies that can increase the variety and availability of these ingredients in the market. •Microorganisms and enzymes can be used for the synthesis of prebiotics compounds.•Prebiotics improve the consistency, elasticity, viscosity and firmness in processed food.•They stimulate the development of bacteria beneficial to the host health.•Their intake is linked to anti-inflammatory and anti-glycemic modulation.•They are an innovation hotspot in food, pharmacy, materials engineering and fine chemicals.